Chemical characterization of Anthemis parlatoreana fresh and dried aerial parts by GC and LC chromatographic techniques and evaluation of the antioxidant properties. (2nd January 2023) - Micalizzi, Giuseppe; Oulad El Majdoub, Yassine; Alibrando, Filippo; Cacciola, Anna; Spadaro, Vivienne; Mondello, Luigi; Germanò, Maria Paola; Cacciola, Francesco
Abstract: Anthemis parlatoreana was collected in the north west coast of Sicily. Fresh and dried aerial parts were subjected to distillation procedure for the extraction and isolation of essential oils. In both fresh and dried samples, the most abundant chemical classes were ketones and esters, represented to a greater extent by β-thujone and β-artemisia acetate, respectively. In dried vegetable material, a high content of α-pinene and δ3-carene was also registered. Aqueous, methanol and ethyl acetate extracts of aerial parts were also investigated in terms of polyphenolic content and antioxidant potential. All the extracts tested showed a quite different quali-quantitative profile and in terms of chemical classes, most of compounds belonged to the hydroxycinnamic class (15 compounds) followed by flavonoid one (11 compounds); the rest was comprised of 2 sequiterpenoids, 2 organic acids and 1 hydroxybenzoic acid derivative. Further, the dried methanolic followed by the dried aqueous extracts revealed the best quenching ability, whereas concerning iron chelating capacity, although all of them showed a marked capacity to disrupt or inhibit the formation of iron (II)-Ferrozine complex, a slight difference was observed between the dried and the fresh ones, since the former have a slightly higher chelating power than the latter.